Fórum educacional digital: dialogismo e construção do conhecimento - Silva, Sandra Gonçalves da (2009)
In this work, we aim to examine traces of dialogism in messages of digital educational forums of a semi-present discipline of a Language Course at Pontifícia Universidade Católica de Sao Paulo. This search occurs from the assumption that, in order to meet the purpose of discussing the topic at issue in the teaching and learning process, the formation and operation of discourses of digital educational forums occur in two ways: restricted dialogue, as a way of interaction, and wider dialogue, as dialogue between discourses, in which the point of view of a message in a digital educational forum is not an isolated construction. In reality, it is a link between the discourses that precede and succeed it. This research aims at contributing to the studies of genres in a discursive domain, yet in the making and called the digital educational forum by Crescitelli, Geraldini and Quevedo (2008). Using the Bakhtinian studies, we carried out an analysis on the dialogic connection of the reaction-response of something just said and the interconnection with the next thing said as well as the strategic marks used in the speech of the other. The results obtained have shown the dialogue as a very important phenomenon in interaction and as a way towards a collaborative construction in digital educational forums